2019
DOI: 10.1186/s12940-019-0541-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between prenatal exposure to perfluoroalkyl substances and asthma in 5-year-old children in the Odense Child Cohort

Abstract: BackgroundAsthma is the most common non-communicable disease in children. Prenatal exposure to perfluoroalkyl substances (PFASs), a group of persistent environmental chemicals with endocrine disrupting abilities, has been associated with immunomodulation and may contribute to the aetiology of asthma. We investigated the associations between prenatal exposure to five PFASs and asthma in 5-year-old children.MethodsWe studied 981 mother-child pairs within the Odense Child Cohort (OCC), Denmark. We measured perflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…A lack of significant findings among childhood asthma diagnosis and/or symptoms (e.g., wheeze) and PFAS levels has been reported by numerous other studies ( Impinen et al., 2018 , 2019 ; Jackson-Browne et al., 2020 ; Smit et al., 2015 ). For example, Beck et al. (2019) examined prenatal exposure to PFOS, PFOA, PFHxS, PFNA, and PFDA and child asthma at the age of 5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lack of significant findings among childhood asthma diagnosis and/or symptoms (e.g., wheeze) and PFAS levels has been reported by numerous other studies ( Impinen et al., 2018 , 2019 ; Jackson-Browne et al., 2020 ; Smit et al., 2015 ). For example, Beck et al. (2019) examined prenatal exposure to PFOS, PFOA, PFHxS, PFNA, and PFDA and child asthma at the age of 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…(2017) , Faroe Island Cohort, cord blood and maternal serum 2 weeks after parturition, child serum at 18 months and 5 years, Faroe Islands, 2007–2009 Age 18 months and 5 years Maternal (n = 55) Geometric mean ± GSE 9.075 ±0.495 1.47 ±0.100 0.789 ±0.056 0.298 ±0.020 N/A N/A N/A 0.24 ±0.022 N/A 18 months old (n = 41) Geometric mean ± GSE 8.25 ±0.761 3.58 ±0.391 1.244 ±0.135 0.347 ±0.033 N/A N/A N/A 0.247 ±0.045 N/A 5 years old (n = 53) Geometric mean ± GSE 5.058 ±0.261 2.596 ±0.128 1.358 ±0.095 0.357 ±0.024 N/A N/A N/A 0.372 ±0.032 N/A Knudsen et al., 2018 , Greenlandic Birth cohort, maternal serum, Greenland 2010–2011 Age N/A All (N = 189) Median (Range) N/A N/A N/A N/A N/A N/A N/A N/A 18.5 (6.14–96.43) Immune Outcome: Asthma Agier et al. (2019) , European Human Early-Life Exposome (HELIX), maternal and child serum, Europe 2003–2009 Age 6–12 years Prenatal (N = 1,033 child-mother pairs) Mean (SD) 8.2 (6.1) 2.6 (1.8) 0.8 (0.6) N/A N/A N/A N/A 0.8 (1) N/A Postnatal (N = 1,033 child-mother pairs) Mean (SD) 2.6 (2.6) 1.7 (0.7) 0.7 (0.7) N/A N/A N/A N/A 0.5 (1) N/A ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found inverse associations between PFOA or PFOS and birth weight. 17,41,48 However, other studies have reported inconsistent associations. [49][50][51] Other outcomes at birth, such as length, BMI, and head circumference, have been investigated with mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested positive associations between maternal exposure to PFAS and low birth weight, 15 dyslipidemia, 16 and asthma in childhood. 17 Age, diet, and maternal characteristics have been identified as maternal predictors of PFOA and PFOS in developed countries. 18 However, there may be different predictors for different populations, and there is limited knowledge about maternal predictors of PFOA and PFOS in developing countries.…”
Section: Introductionmentioning
confidence: 99%